Предмет: Математика,
автор: sushkolena21
спростіть вирази 15*(2+b)+3*(12-b)=
Ответы
Автор ответа:
0
Ответ:
66 + 12b
Пошаговое объяснение:
15(2+b) = 15*2 + 15*b = 30+15b
3(12-b) = 3*12 - 3*b = 36-3b
Следовательно, 15(2+b) + 3(12-b) = 30+15b+36-3b = (30+36)+(15b-3b) = 66 + (15-3)b = 66 + 12b
Похожие вопросы
Предмет: Українська мова,
автор: pirdarina5
Предмет: Математика,
автор: p32811386
Предмет: История,
автор: protopopovvladislav0
Предмет: Алгебра,
автор: kiminna72
Предмет: Математика,
автор: kotemote0